How Do Underwriters Select Peers When Valuing IPOs?. Issue 4 (22nd October 2014) - Paleari, Stefano; Signori, Andrea; Vismara, Silvio
Abstract : Valuing initial public offerings (IPOs) using multiples allows underwriters discretion when selecting comparable firms. We find that they systematically exclude candidate comparable firms that make a given IPO appear overvalued. On average, comparable firms published in official prospectuses have 13%‐38% higher valuation multiples than those obtained from matching algorithms or selected by sell‐side analysts, including the same underwriter's analyst after the IPO. Even if IPOs are priced at a discount as compared to peers selected by the underwriters, they are still at a premium with regard to alternatively selected peers. Greater bias in the underwriter's selection of peers leads to poorer long run performance.